DETERMINAN FRAUDULENT FINANCIAL REPORTING DALAM PERSPEKTIF TRIANGGLE FRAUD - Saraswati Ayu Hapsari; Almatius Setya Marsudi (Prosiding Working Papers Series In Management, 2018)
This research aims to examine determinant of financial fraud reporting. The population in this research is the manufacturing company registered in Indonesia stock exchange in 2014-2016, in which there are 30 companies as the samples of research. The hypothesis be examined with multiple linear regression analysis. The research shows that financial targets effect on fraudulent financial reporting and effectiveness of supervision influences fraudulent financial reporting. Keywords: fraudulent financial reporting, financial target, effectiveness.